2020
DOI: 10.1051/e3sconf/202019708012
|View full text |Cite
|
Sign up to set email alerts
|

High-reflective Mulching Membrane for a Sustainable Development: Monitoring Campaign

Abstract: Modern agriculture techniques are responsible for the production of large volumes of greenhouse gases that represent the main cause of climate change. At the same time, agricultural activities are negatively affected by climate change effects, showing a reduction in productivity. Within this framework, the present study aims at investigating the effectiveness of an innovative high-reflective mulching membrane that can be exploited in the agricultural sector to mitigate its environmental impact. It consists of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 14 publications
0
7
0
1
Order By: Relevance
“…Water resistance property of such a membrane enables collecting rainwater that is exploited for irrigation purposes. A preliminary investigation has already demonstrated that this can positively influence plant growth [14]. Nonetheless, membrane's influences on plant growth cycle and soil humidity are worth further investigation and they will be assessed in future studies.…”
Section: Materials Characterizationmentioning
confidence: 96%
See 1 more Smart Citation
“…Water resistance property of such a membrane enables collecting rainwater that is exploited for irrigation purposes. A preliminary investigation has already demonstrated that this can positively influence plant growth [14]. Nonetheless, membrane's influences on plant growth cycle and soil humidity are worth further investigation and they will be assessed in future studies.…”
Section: Materials Characterizationmentioning
confidence: 96%
“…Within this framework, new and more sustainable technologies such as mulching membranes, advanced irrigation systems, water recovery plants, and high-efficiency greenhouse infrastructures were implemented to further enhance the growth process and the yield of food crops, while reducing their ecological footprint [10][11][12]. Highly reflective materials that had been demonstrated to be a valid solution to reduce global temperature [13], were proposed for the agricultural sector [14]. Their cooling potential was assessed at various latitudes [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The field comprised 12 beds with 12 plants, each covered by a highly reflective membrane, and two beds without cover, with 12 plants each, for a total surface area of 120 m 2 , with a 15% slope (Figure 1). The high-reflective-mulch-covered area was more extensive because previous experiments required air temperature measurement at different locations, with the uncovered area as a control [7]. The rainwater collected by the membrane was gravity-drained and stored in an underground tank.…”
Section: System Description and Boundariesmentioning
confidence: 99%
“…Mulch covers are extensively employed in agriculture. The method helps maintain suitable soil temperature and to control humidity, inhibits erosional processes and nutrient losses, and improves water management [6,7]. Given the widespread application of mulch covers, much research has focused on assessing the environmental impacts of the practice [8][9][10] and developing more sustainable materials for its application [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation